Music and Identity: Immortal Rites’ Art as the Narrative of Contemporary Kejawen Identity - Akhtabi, Petrik Mahisa; Puryanti, Lina (Harmonia: Journal of Arts Research and Education, 2022)
This study explores the context of identity in the musical arts echoed by a Black Metal band from Kediri, Immortal Rites. Aesthetically, Immortal Rites articulate Javanese locality using Black Metal, a sub-genre of underground music that emerged in Indonesia in the late 90s. Accordingly, the band lined up as one of the Kejawen Black Metal whose consistency and depth of understanding are well appreciated within the scene. The unification of two different cultures provokes a complex contemporary value of a cultural reflection concerning identity. This study uses a qualitative research method with a descriptive approach. This study aims to discuss the narrative of identity that Immortal Rites wish to embody for its fans to understand. By focusing analysis on the main data of song lyrics with additional data in the form of interviews, we found that the echoed locality represents a notion of contemporary Javanese identity. Within the arts, there was a close relevance of the content with the identical Javaneseness in the era of the Kadiri kingdom. Thus, based on the engagement of the arts and the Kediri-based Javaneseness, it leads us to an understanding of the mediated cultural representation of contemporary Javanese identity, of a Daha-based Javanese identity.